STRESS PASIEN DENGAN ULKUS KAKI DIABETIKUM DI AL HIJRAH WOUND CARE CENTER JOMBANG: The Study of Stress Patients With Diabetic Ulcers in Al Hijrah Wound Care Center - Fahruddin Kurdi; Anja Hesnia Kholis; Nurul Hidayah; Maya Fitriasari (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2020)
ABSTRACT Diabetic foot ulcer is a complication of mellitus. The complication can cause psychological problems that cause stress for patient. The severity of diabetic foot ulcer will increase stress in patients. To deal with stress that needs to be overcome by reducing stress independently, besides the support system of the family is needed to help reduce stress and psychological burden. The purpose of this research is to explore how stress is experienced by diabetic foot ulcer patient. This research is a qualitative research with phenomenology approach. Participants were diabetic ulcer who come for wound care treatments at Al Hijrah wound care center, as well as the nuclear family as additional informants. Data is taken with a thorough interview, observation. The results obtained from two participants that stress due to diabetic ulcers is a condition related to physical and psychological conditions that cause participants to increase stress, such as: body image disorders, immobility, fear to amputation and cost difficulties. The main effort to reduce stress is pray, read the Al Quran, dzikr and ask for help to health services in the hope that the stress can reduced independently and does not cause worse complications. It is hoped that further research will examine more deeply the stress experienced by patients with diabetic ulcers.